2016
DOI: 10.1186/s13018-016-0476-9
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis on the correlation between hip pain, physical examination findings, and alpha angle on MR images

Abstract: BackgroundWe aimed to search whether alpha angle, a radiological clue used in the diagnosis of femoroacetabular impingement, is correlated with the presence of hip pain, internal rotation angle, and impingement test results on hip impingement patients (CAM type).MethodsMedical records of 334 patients (156 women, 178 men) with an average age of 33.8 ± 8.4 (range 20–50) years were retrospectively studied for the alpha angle of the hip measured on magnetic resonance images (MRI). Hip pain and internal rotation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…Clinical studies confirm have confirmed this by observing that patients with larger cam lesions report greater pain at lower ranges of motion. 35 Synthesizing our findings with the previous in vivo hip translation literature, we propose that hip translation depends on a combination of osseous factors, soft-tissue laxity, and hip position. Osseous factors promoting greater hip translation include poor acetabular coverage in the setting of acetabular dysplasia and larger alpha angles.…”
Section: Discussionsupporting
confidence: 78%
“…Clinical studies confirm have confirmed this by observing that patients with larger cam lesions report greater pain at lower ranges of motion. 35 Synthesizing our findings with the previous in vivo hip translation literature, we propose that hip translation depends on a combination of osseous factors, soft-tissue laxity, and hip position. Osseous factors promoting greater hip translation include poor acetabular coverage in the setting of acetabular dysplasia and larger alpha angles.…”
Section: Discussionsupporting
confidence: 78%
“…Allen et al 18 demonstrated a significant association between higher alpha angles in painful hips (mean 69.9°) than in asymptomatic hips (mean 63.1°). In a retrospective study of 334 patients, a significant association between hip symptoms and increased alpha angles ( P < .001) was observed as well 34 …”
Section: Discussionmentioning
confidence: 92%
“…They found that pain was more commonly present in players with cam or mixed morphology, though only larger cam morphologies (increasing α-angle without specified cutoff value) were predictive for hip pain [5]. Furthermore, in a retrospective study by Guler et al, the α-angle was shown to be significantly higher in those with hip pain (55.9°) compared with those without (52.7°) [22]. An interpretation of this could mean that larger cam morphological changes might be painful earlier compared with smaller cam morphological changes that take longer to develop pain.…”
Section: Discussionmentioning
confidence: 97%
“…It is possible that this may explain the low or absence of a correlation between hip pain and the presence and size of cam morphology in this study. Both Khanna et al and Guler et al included a general population with a mean age of 29.5 and 33.8 years, respectively [22,23], and therefore had more years to develop hip pain. The duration of which cam morphology may have been present in this study might have been too short.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation